Carbohydrate antigen 125 supplements carbohydrate antigen 19-9 for the prediction of invasive intraductal papillary mucinous neoplasms of the pancreas - Yunzhen Qian; Yitao Gong; Guopei Luo; Yu Liu; Ruijie Wang; Xuan Zou; Shengming Deng; Xuan Lin; Yusheng Chen; Xu Wang; Xianjun Yu; He Cheng; et al. (World Journal of Surgical Oncology, 2022)
Abstract Background Intraductal papillary mucinous neoplasms (IPMNs) are characterized by their abundant mucin production and malignant potential. IPMNs of the pancreas are mainly managed according to their radiographic indications, but this approach lacks accuracy with regard to IPMN grading. Therefore, serological biomarkers such as CA19-9 and CA125 (MUC16) should be employed to assist in predicting the invasiveness of IPMNs. Methods We investigated the preoperative serum levels of CA19-9, CA125 and CEA in 381 surgical patients with a definite pathological diagnosis of IPMN from July 2010 to December 2019 at the Shanghai Cancer Center. We calculated the Youden indices of each point on the receiver operating characteristic (ROC) curves to identify the most appropriate cut-off values of CA19-9, CA125 and CEA for recognizing malignant IPMNs. Serological biomarker differences were correlated with clinicopathological features of IPMNs, and diagnostic indices of different scenarios were calculated to find the optimum strategy. Results The malignant group had higher serum levels of CA19-9, CA125 and CEA. According to the ROC curves, the cut-off values of CA19-9, CA125 and CEA were readjusted to 38.3 U/ml, 13.4 U/ml and 5.3 μg/L. CA19-9 elevation was significantly associated with vascular invasion and perineural infiltration. CA125 showed good efficacy in predicting invasive IPMN in the CA19-9-negative subgroup. Conclusions Serological biomarkers are useful and sensitive indicators for recognizing invasive IPMNs. CA19-9 is the most important diagnostic index among all routinely measured serum biomarkers for differentiating malignant from benign IPMNs. CA19-9 should be combined with CA125 to enable more accurate predictions of IPMN malignancy.